The International Yoga Day, political discourse, and soft power game in India - Janmejaya Samal (Wolters Kluwer Medknow Publications, 2020)
The International Day of Yoga is being celebrated every year on 21st June since 2015, throughout the globe. The United Nations (UN) General Assembly on December 11, 2014, declared that 21st June would be celebrated as the International Day of Yoga or World Yoga Day following lobbying by the Prime Minister of India, Mr Narendra Modi. One hundred and seventy countries around the globe supported the resolution which even did not require vote. Mr Narendra Modi, in his address to the UN in September 2014, stated that it is not about the exercises rather the way of discovering oneself. Furthermore, he stated that it is the longest day of the Northern Hemisphere and has special significance in many parts of the world. It is the day of summer solstice. It is now being celebrated beyond religion, region, and culture, however, it has been politicized since its first day of observation. It is neither an innocent event nor dissociated from politics and soft power game in India. Despite all these, many believe that it would live up to its lofty ideals and that these become its eternal legacy.